2021
DOI: 10.3390/jcm10102062
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid—An Emergent Risk Marker for Thrombosis?

Abstract: Hyperuricemia is nowadays an established cardiovascular risk factor. Experimental studies linked elevated serum uric acid (SUA) levels with endothelial dysfunction (ED), inflammation, and prothrombotic state. The purpose of this review is to summarize the current evidence that emphasizes the possible role of uric acid as a biomarker for a prothrombotic state. A large number of clinical trials correlated SUA levels with both incident and recurrent cases of venous thromboembolism (VTE), independent of other conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
0
14
1
Order By: Relevance
“…UA can cause vascular damage through a variety of mechanisms, and elevated UA levels are associated with endothelial dysfunction, inflammation, and a prothrombotic state. Therefore, UA can be used as a biomarker for the prothrombotic state [ 28 ]. Proximal pulmonary artery dilatation was observed on echocardiography PE, suggesting possible pulmonary hypertension or high right ventricular overload.…”
Section: Discussionmentioning
confidence: 99%
“…UA can cause vascular damage through a variety of mechanisms, and elevated UA levels are associated with endothelial dysfunction, inflammation, and a prothrombotic state. Therefore, UA can be used as a biomarker for the prothrombotic state [ 28 ]. Proximal pulmonary artery dilatation was observed on echocardiography PE, suggesting possible pulmonary hypertension or high right ventricular overload.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between serum uric acid levels and cardiovascular diseases (CVD) may not be J-shaped. Previous studies have reported that an approximate U-shaped association between serum uric acid levels and 10-year CVD risk scores exists in men, while a J-shaped association existed in women [ 24 ]. Uric acid levels were obviously higher in young patients with STEMI in this study than in older patients, although the value did not exceed the upper limit.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum UA level is associated with a wide range of diseases such as hypertension, chronic kidney disease, heart failure, and coronary artery disease, all these making it an important risk diagnostic tool [ 32 ]. Uric acid has been shown to be a useful biochemical marker of endothelial function, atherosclerosis, development of cardiovascular risk factors, and occurrence of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%